Magic & Bird [videorecording (DVD)] : a courtship of rivals - Edelman, Ezra; Schreiber, Liev (Home Box Office, 2010)
For years, the passion they shared for winning made Earvin 'Magic' Johnson and Larry Bird the most bitter of rivals. It also made theirs the most compelling rivalry in sports, driving the NBA to new heights of popularity in the 1980s. This all-new documentary tells the riveting story of two superstars who couldn't have been more different, until they forged an unlikely friendship from the superheated rivalry that had always kept them apart.